The association between under-nutrition, school performance and perceptual motor functioning in first-grade South African learners: The North-West Child Health Integrated with Learning and Development study - Anita E. Pienaar (AOSIS, 2019)
Background: Early childhood is characterised by an immense spurt of growing and learning where under-nutrition can have adverse effects on the neuro-developmental health and school performance of children. A full understanding of the relationship between school performance and motor functioning skills and malnourishment in school beginners is still lacking. Aim: To determine the association between indices of under-nutrition and how it relates to school performance and motor functioning skills of first-grade learners. Setting: North West province (NWP) of South Africa (SA). Method: The baseline data of the stratified, randomised North-West Child Health Integrated with Learning and Development (NW-CHILD) longitudinal study were used. Grade 1 learners (N = 816, 420 boys, 396 girls, mean age 6.78+ years) from four school districts in the NWP of SA took part in the study. Indices of under-nutrition were determined by Z-scores (−2 standard deviation [s.d.]) for stunting (height-for-age [HAZ]) and wasting and underweight (Z-score for body mass index) using the 2007 World Health Organization reference sample. The Bruininks-Oseretsky Test of Motor Proficiency Short Form and the Visual Motor Integration fourth edition were used to assess different aspects of motor functioning, while school performance in mathematics, reading and writing was assessed by teachers according to the National South African standards of assessments. Results: Both HAZ and Z-score for weight-for-age correlated significantly with school performance and motor functioning skills (r 2.0, p 0.05), while visual perception was moderately associated (r 0.30) with mathematics in HAZ and Z-score for weight-for-height (WHZ) children. Motor functioning of HAZ and WHZ children was significantly poorer (p 0.05) compared to typical children, while underweight was not associated with any outcome variables. Conclusion: Moderate forms of stunting and wasting influence school performance and motor functioning of school beginners negatively, while an association between visual perceptual abilities and inferior mathematics, reading and writing suggests a close link with inferior cognitive information processing in stunted and wasted children. These barriers should be addressed as poor scholastic success in Grade 1 may influence future school performance and the subsequent well-being of children.